2022
DOI: 10.3389/fmolb.2022.922839
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Mechanism of Drug Resistance Caused by the T790M Mutation in EGFR Kinase From Absolute Binding Free Energy Calculations

Abstract: The emergence of drug resistance may increase the death rates in advanced non-small cell lung cancer (NSCLC) patients. The resistance of erlotinib, the effective first-line antitumor drug for NSCLC with the L858R mutation of epidermal growth factor receptor (EGFR), happens after the T790M mutation of EGFR, because this mutation causes the binding of adenosine triphosphate (ATP) to EGFR more favorable than erlotinib. However, the mechanism of the enhancement of the binding affinity of ATP to EGFR, which is of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…A recent in-depth in silico study showed that the higher inhibitory activity showed by BLU-945's derivatives, compared to Erlotinib, is due to the formation of HBs with Lys728, Lys745, and Thr854, wherein the piperidinol and sulfone groups seem to be the greatest contribution to the binding energy observed in the EGFR mutants 74 (Figure 9). The X-ray structure of compound 14 in complex with EGFR L858R/ T790M (PDB 8D76) clearly shows the involvement of these amino acids in the binding's stabilization in addition to the classical anchoring of the TKIs to the hinge region through the aminopyridine moiety (Figure 9A).…”
Section: 4-bis-anilinopyrimidine Containingmentioning
confidence: 99%
“…A recent in-depth in silico study showed that the higher inhibitory activity showed by BLU-945's derivatives, compared to Erlotinib, is due to the formation of HBs with Lys728, Lys745, and Thr854, wherein the piperidinol and sulfone groups seem to be the greatest contribution to the binding energy observed in the EGFR mutants 74 (Figure 9). The X-ray structure of compound 14 in complex with EGFR L858R/ T790M (PDB 8D76) clearly shows the involvement of these amino acids in the binding's stabilization in addition to the classical anchoring of the TKIs to the hinge region through the aminopyridine moiety (Figure 9A).…”
Section: 4-bis-anilinopyrimidine Containingmentioning
confidence: 99%
“…Shigeto et al (2020) used single-cell microarray chips and peptide nucleic acid (PNA)-DNA probes to specifically detect T790M mutant cancer cells. Among secondary drug resistance mutations, EGFR-mutant phenotypes are most common in NSCLC due to mutations in the receptor-binding region of the EGFR gene (T790M) driving secondary mutations in the kinase domain, reducing the affinity of tumour cells for targeted therapies (Sun et al, 2022;Zhou et al, 2022). Tyrosine kinase inhibitors (TKIs), as represented by gefitinib, are molecularly targeted anticancer drugs that bind to the structural domain of the EGFR protein tyrosine kinase (Lynch et al, 2004;Yun et al, 2008), inducing cell death by inhibiting the signal transduction of epidermal growth factor (Kobayashi and Mitsudomi, 2016).…”
Section: Screening For Drug-resistant Cancer Cellsmentioning
confidence: 99%
“…12,13 The T790M mutation decreases the drug efficacy by increasing the ATP affinity of the EGFR mutant and hindering drug binding. 14,15 Third-generation EGFR TKIs, such as osimertinib, have been developed to address this issue and have shown remarkable clinical efficacy in first-and second-line treatment. 16,17 However, the emergence of a tertiary mutation, C797S (Figure 1A), disrupts the covalent binding of the inhibitor and presents a new challenge for drug design.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Lung cancer is the leading cause of cancer-related deaths worldwide, with non-small-cell lung cancer (NSCLC) accounting for 80–85% of cases. , NSCLC is characterized by the overexpression or mutation of the kinase domain of the epidermal growth factor receptor (EGFR), leading to uncontrolled cell growth and division. Exon 19 deletions (Del19) or a single missense mutation in exon 21 (L858R) are the most common EGFR activating mutations in NSCLC (Figure A) . Over the past two decades, EGFR tyrosine kinase inhibitors (TKIs), such as the reversible first-generation ATP-competitive inhibitor erlotinib (Figure B) and the irreversible second-generation EGFR inhibitor afatinib, have been developed and have demonstrated effectiveness in treating patients with Del19 and L858R mutations. , However, the majority of patients eventually develop resistance to these TKIs, often within 1–2 years of treatment, and experience disease progression. , Resistance most commonly arises due to the emergence of a secondary mutation in the gatekeeper residue (T790M) (Figure A), which is observed in 50–70% of patients treated with first- and second-generation EGFR inhibitors. , The T790M mutation decreases the drug efficacy by increasing the ATP affinity of the EGFR mutant and hindering drug binding. , Third-generation EGFR TKIs, such as osimertinib, have been developed to address this issue and have shown remarkable clinical efficacy in first- and second-line treatment. , However, the emergence of a tertiary mutation, C797S (Figure A), disrupts the covalent binding of the inhibitor and presents a new challenge for drug design. …”
Section: Introductionmentioning
confidence: 99%